PENGARUH BEBAN KERJA, STRES KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN CV. KAMPOENG SEJAHTERA - Didik Hariyanto; Hadi Sunaryo; A. Agus Priyono (UNIVERSITAS ISLAM MALANG, 2019)
ABTRACKThe aims of recent study are to portray the workload, work stress, organizational climate, and employee performance of CV Kampoeng Sejahtera in Malang and to investigate whether workload, work stress, and organizational climate simultaneously and partially have effect on employee performance of CV Kampoeng Sejahtera or not. This study involved 98 out of 130 employees as the sample. The sampling technique was proportional random sampling, in which takes consider on elements or categories in the population to be chosen as a sample. The instrument being used was questionnaire and document analysis. Then, the data were analyzed by using descriptive statistics and multiple regression analysis. The result revealed that (1) workload, work stress, and organizational climate had simultaneous effect to employee performance, (2) workload positively and significantly effected to employee performance, (3) work stress positively and significantly influenced on employee performance, as well as (4) organizational climate had positive and significant effect to employee performance. Keywords: workload, work stress, organizational climate, employee performance